Pengembangan Media Pembelajaran Interaktif Speaking Pyramid untuk Meningkatkan Penguasaan Kosa Kata Bahasa Inggris Anak Usia 5-6 Tahun - Muliana, Husnul; Warmansyah, Jhoni (JOSTECH: Journal of Science and Technology, 2022)
This research aims to produce a valid and practical speaking pyramid interactive learning media so that it can attract children's attention in the learning process. The type of research used is research and development (R&D) using a 4D development model, in research that only goes up to three stages, namely defining, designing and developing. The research was conducted at An-Nur Sungai Batuang Kindergarten with the type of data collection instrument using a validation sheet and a practicality sheet (teacher response questionnaire). From the research, it was found that the speaking pyramid interactive learning media was very valid with a percentage of 86.25% and very practical with a percentage of 87.5%. Thus the interactive learning media speaking pyramid is feasible and can be used by teachers in improving English vocabulary mastery for early childhood.